Trends in subjective income poverty rates in the European Union - Tomáš Želinský; Martina Mysíková; Thesia I. Garner (The European Journal of Development Research, 2021)
When developing anti-poverty policies, policymakers need accurate data on the prevalence of poverty. In this paper, we focus on subjective poverty, a concept which has been largely neglected in the literature, though it remains a conceptually appealing way to define poverty. The primary goal of this study is to re-examine the concept of subjective poverty measurement and to estimate trends in subjective income poverty rates in the European Union. Our estimations are based on a Minimum Income Question using data from a representative survey, EU-SILC. We find robust empirical evidence of decreasing trends in subjective poverty in 16 of 28 EU countries. We conjecture that trends in subjective poverty may reflect changes in societies which are not captured by official poverty indicators, and our results thus enrich the existing data on general poverty trends in the EU. – – Lors de l'élaboration des politiques de lutte contre la pauvreté, les décideurs ont besoin de données précises sur la prévalence de la pauvreté. Dans cet article, nous nous concentrons sur la pauvreté subjective, un concept qui a été largement négligé dans la littérature, bien qu'intéressant pour définir la pauvreté. L'objectif principal de cette étude est de réexaminer le concept de mesure subjective de la pauvreté et d'estimer les tendances des taux de pauvreté monétaire subjective dans l'Union européenne. Nos estimations sont basées sur une question relative au revenu minimum en utilisant les données d'une enquête représentative, EU-SILC. Nous trouvons des preuves empiriques solides que la pauvreté subjective a tendance à baisser dans 16 des 28 pays de l'UE. Nous supposons que les tendances de la pauvreté subjective peuvent refléter des changements sociétaux qui ne sont pas pris en compte par les indicateurs officiels sur la pauvreté. Ainsi, nos résultats viennent enrichir les données existantes sur les tendances générales de la pauvreté dans l'UE.
Keywords: I31; I32; 330; Subjective poverty; Minimum Income Question; intersection approach; EU-SILC; European Union